PENDIDIKAN BERPERSPEKTIF GENDER DI PESANTREN - Hamam Burhanuddin (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2015)
Abstract: Gender in Pesantren become interesting issue to be studied, Islam teaches about equality (musawamah) means similarity conditions for men and women as well as the opportunity to obtain their rights as human beings, to be able to contribute and participate in political activities, law, economics, social, cultural, educational. Gender equality also includes the elimination of discrimination and structural, both men and women. The realization of gender equality is characterized by the absence of discrimination between women and men, and they have access, to participate and control over the development and the benefits equal and fair share of development, in this study the authors examine gender from the standpoint of education, Islamic concepts offered are al musawamah, al ‘adalah, tawazun, tawasut, taadud, al ‘adalah, tahiyyah, ukhuwah. There are can be applied in education in Pesantren.  Some discourse underlying the need for educational efforts to socialize gender perspective, namely as awareness efforts against injustice in social life. Gender socializing can be started from several educational institutions, both formal and non-formal, one of them through education in schools.